Effect of Striped Catfish (Pangasianodon Hypophthalmus) Supplementation on Mice (Mus Musculus) Colon - Wibowo, Agung Ary; Hosea, Nathania; Triawanti, Triawanti; Lahdimawan, Ardik; Priyono, Sasongko Hadi; Siagian, Andreas Marojohan Haratua; Sikumbang, Kenanga Marwan (Faculty of Medicine, Universitas Padjadjaran, 2025)
Diet affects the microbial structure of the gut and human metabolic functions. Disruption of nutrient sources that produce short-chain fatty acids (SCFA) will cause atrophy and inflammation of the colonic mucous. Striped catfish (Pangasianodon hypophthalmus) increases SCFA production because of its high levels of carbohydrates, protein, and fat content. This experimental study used 50 male mice (Mus musculus) aged 3 months old, weighing 20-30 grams, divided into control group (given standard feed) and treatment group (given mixture of standard feed and striped catfish meat). The mice were given treatment for eight (8) weeks at the Faculty of Medicine and Health Sciences, Lambung Mangkurat University, Indonesia, from May to July 2024 and then sacrificed. Colon biopsies were examined using hematoxylin-eosin staining to determine crypt morphology, number of goblet cells, and number of inflammatory cells at Ulin Hospital Banjarmasin, Indonesia, from July until October 2024. The crypt morphology in the treatment group showed fewer abnormalities (5 out of 25 samples) compared to the control group (11 out of 23 samples) (p=0.041) with a moderate correlation (p=0.295). The number of goblet cells was higher in the treatment group (200.4±54.1) than in the control group (134.5±34.3) (p=0.001) with a strong correlation (p = 0.616). The number of inflammatory cells was lower in the treatment group (9.9±4.4) than in the control group (27.6±7.8) (p=0.001) with a very strong correlation (p=0.838). Thus, striped catfish supplementation reduces morphological abnormalities of the crypts and the number of inflammatory cells, as well as increases the number of goblet cells in the colon of mice.